Influence of Detector Size and Positioning on Near-Infrared Measurements and Iso-pathlength Point of Turbid Materials - Duadi, Hamootal; Feder, Idit; Fixler, Dror (Frontiers in Physics, 2021)
Measuring physical phenomena in an experimental system is commonly limited by the detector. When dealing with spatially defined behaviors, the critical parameter is the detector size. In this work, we examine near-infrared (NIR) measurements of turbid media using different size detectors at different positions. We examine cylindrical and semi-infinite scattering samples and measuring their intensity distribution. An apparent crossing point between samples with different scatterings was previously discovered and named the iso-pathlength point (IPL). Monte Carlo simulations show the expected changes due to an increase in detector size or similarly as the detector’s location is distanced from the turbid element. First, the simulations show that the intensity profile changes, as well as the apparent IPL. Next, we show that the average optical pathlength, and as a result, the differential pathlength factor, are mostly influenced by the detector size in the range close to the source. Experimental measurements using different size detectors at different locations validated the influence of these parameters on the intensity profiles and apparent IPL. These findings must be considered when assessing optical parameters based on multiple scattering models. In these cases, such as NIR assessment of tissue oxygenation, the size and location may cause false results of absorption or optical path.